Adoption of Mobile Marketing in the Telecommunication Industry of Tanzania: The Effects of Perceived Usefulness, Ease of Use, and Customer’s Knowledge - Felix Joseph Chille; France Aloyce Shayo; Nasra Shokat Kara (European Scientific Journal, ESJ, 2021)
This paper focuses on identifying the factors affecting customer’s adoption of mobile marketing by examining the effects of perceived usefulness, perceived ease of use, and perceived customer’s knowledge in the telecommunications industry of Tanzania. The study extended the Technology Acceptance Model (TAM), with Diffusion of Innovation Theory (DOI), in predicting the customer’s mobile marketing adoption. Survey strategy was employed in data collection by administering the structured questionnaires and collected data using multi stage sampling on 406 respondents in Dar es Salaam. After then, it was analyzed using factor analysis, correlation analysis, and multiple linear regression analysis. Findings indicated that perceived usefulness, perceived ease of use, and perceived customer knowledge have significant and positive influence on the adoption of mobile marketing in the telecommunication industry in Tanzania. The study contributes to telecommunication practitioners with the integrated theoretical framework, which suggest that telecommunication practitioners need to develop mobile platforms that are easy to use, useful in solving customers’ problems and in designing products whose benefits are easily understood by customers. Through holistic mobile marketing approach, this study makes parsimonious contribution to knowledge by using few variables in predicting the customer’s adoption of mobile marketing in Telecommunication industry in Tanzania.